Microenvironment commits breast tumor ECs to dedifferentiation by micro-RNA-200-b-3p regulation and extracellular matrix remodeling - Wilkus-Adamczyk, Kinga; Brodaczewska, Klaudia; Majewska, Aleksandra; Kieda, Claudine (Frontiers in Cell and Developmental Biology, 2023)
Introduction: Hypoxia shapes the tumor microenvironment, modulates distinct cell population activities, and activates pathological angiogenesis in cancer, where endothelial cells (ECs) are the most important players. This study aimed to evidence the influences of the tumor microenvironment on the global gene expression pattern characteristic for ECs and the distinct responses displayed by tumor-derived ECs in comparison to the healthy endothelium during endothelial to mesenchymal transition (EndMT) and its regulation by miR-200-b-3p. Methodology: Immortalized lines of ECs from the same patient with breast cancer, healthy breast tissue (HBH.MEC), and primary tumor (HBCa.MEC) were used. The experiments were performed in normoxia and hypoxia for 48 h. By using the wound healing test, we investigated the migration abilities of ECs. Global gene expression analysis with NGS was carried out to detect new pathways altered in pathological ECs and find the most changed miRNAs. The validation of NGS data from RNA and miRNA was estimated by qPCRs. Mimic miR-200b-3p was used in HBH.MEC, and the targets VEGF, Bcl2, ROCK2, and SP1 were checked. Results: Hypoxia influences EC migration properties in wound healing assays. In hypoxia, healthy ECs migrate slower than they do in normoxia, as opposed to HBCa.MEC, where no decreased migration ability is induced by hypoxia due to EndMT features. NGS data identified this process to be altered in cancer ECs through extracellular matrix (ECM) organization. The deregulated genes, validated by qPCR, included SPP1, ITGB6, COL4A4, ADAMST2, LAMA1, GAS6, PECAM1, ELN, FBLN2, COL6A3, and COL9A3. NGS also identified collagens, laminins, fibronectins, and integrins, as being deregulated in tumor-derived ECs. Moreover, the analysis of the 10 most intensively modified miRNAs, when breast tumor–derived ECs were compared to healthy ECs, shed light on miR-200b-3p, which is strongly upregulated in HBCa.MECs when compared to HBH.MECs. Discussion and conclusion: The pathological ECs differed significantly, both phenotypically and functionally, from the normal corresponding tissue, thus influencing their microenvironment cross-talk. The gene expression profile confirms the EndMT phenotype of tumor-derived ECs and migratory properties acquisition. Moreover, it indicates the role of miR-200b-3p, that is, regulating EndMT in pathological ECs and silencing several angiogenic growth factors and their receptors by directly targeting their mRNA transcripts.